2018
DOI: 10.1016/j.psychres.2018.05.058
|View full text |Cite
|
Sign up to set email alerts
|

Occupational stress and suicidality among firefighters: Examining the buffering role of distress tolerance

Abstract: Past research indicates that firefighters are at increased risk for suicide. Firefighter-specific occupational stress may contribute to elevated suicidality. Among a large sample of firefighters, this study examined if occupational stress is associated with multiple indicators of suicide risk, and whether distress tolerance, the perceived and/or actual ability to endure negative emotional or physical states, attenuates these associations. A total of 831 firefighters participated (mean [SD] age = 38.37y[8.53y];… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
36
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 50 publications
(42 citation statements)
references
References 51 publications
(81 reference statements)
4
36
1
1
Order By: Relevance
“…30 , 32 Research even found rates of suicidal ideation and attempts in firefighters to be 46.8% and 15.5%, respectively. 33 , 34 In China, however, there have not been many studies which focused on mental health in firefighters, and the results have not been consistent. Rui et al 35 investigated the mental health of firefighters using the SCL-90 and found that their overall mental health was significantly better than that of local and military populations.…”
Section: Discussionmentioning
confidence: 99%
“…30 , 32 Research even found rates of suicidal ideation and attempts in firefighters to be 46.8% and 15.5%, respectively. 33 , 34 In China, however, there have not been many studies which focused on mental health in firefighters, and the results have not been consistent. Rui et al 35 investigated the mental health of firefighters using the SCL-90 and found that their overall mental health was significantly better than that of local and military populations.…”
Section: Discussionmentioning
confidence: 99%
“…Relatedly, body vigilance—attending to internal cues—is exaggerated in individuals with anxiety‐related pathology (Schmidt, Lerew, & Trakowski, ), converging with our findings. Moreover, anxiety sensitivity, the fear of anxiety‐related sensations (Taylor et al, ), is implicated in suicide risk (see I. Stanley et al, for review) and has been found to statistically explain the link between PTSD symptoms and suicide risk within samples of firefighters (Boffa et al, ; Stanley et al, ). Thus, there is conceptual coherence to our empirical finding that merely observing internal sensations related to PTSD might potentiate suicide risk.…”
Section: Discussionmentioning
confidence: 99%
“…Especially, a previous study conducted in four countries -Korea, China, Australia, and Germany -reported that occupational stress, such as job strain, organizational injustice, and effort-reward-imbalance was associated with suicidal ideation [47]. Recently, the association between suicidality and occupational stress such as discrimination, inadequate pay, disruption of sleep, and concern about serious injury was reported among firefighters [48]. However, it has not yet been investigated whether occupational stress from a difficult physical environment of workplace is associated with suicidal ideation in workers.…”
Section: Discussionmentioning
confidence: 99%